Elaboración de un modelo de gestión administrativa para la cooperativa de ahorro y crédito “Unión” de la ciudad de Loja - Peña Castro, Christian Augusto (2015)
Modern managementstates thatthe success of anycompany or organization,basically depend onthedynamicsofits managementand proper useand exploitation ofdifferentmanagement systemson theprevailingcontemporary world. Corporatemanagers shouldbear in mind that: Quality is not constant,that their achievementshouldbe permanent andmetaperfection. Takingas its premisethe considerationsmentionedin the preceding paragraphsis thatinitiated thepreparation of thisthesis, which originallyhad as itsoverall objectivewas given: Designing anAdministrative ManagementModelfor CooperativeSavings "Union" of the city ofLoja, Year 2014-2015. The methodology usedduring the developmentof thisresearchwas based onthe useof the following methods: Historical MethodDeductiveMethod, Inductive Method, Analytical Method, and Statistical Method; likewise,were appliedthe followinginformationcollection techniques: Observation, Interview, and Survey. It should be notedin thischapter thatsurveyshad to be appliedto all7 employeesof the Cooperative;likewise, a personalinterview was conductedto its General Manager. Based on serious research and development of this thesis I conclude stating: The credit union " Union " of the city of Loja, is a financial organization that enjoys broad public acceptance at the regional level, however its administrative processes lack the technical backing to ensure its continuity and corporate development; because no planning activities to ensure the effective and efficient discharge of their primary goals and corporate objectives which does not allow that invigorate and ensure fully the proposal run